PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN BAHASA DAN KOGNITIF PADA ANAK USIA DINI ( Studi Pada Kelompok A Kelurahan Talang Ulu ) - Titik Harliza; Nina Kurniah (UNIB Press, 2020)
This study aims to develop interactive media to improve language and cognitive skills in early childhood. The research method used was the Borg and Gall Research and Development (R&D) method with 10 development steps. Based on the results obtained, it can be concluded: (1) Based on the validation of media experts and material experts, this interactive media falls into the